The Implementation of K3 Culture Towards Employee Productivity - Umar, Risa Bernadip; Tahir G, Muhammad; Nuryani, Siti; Betan, Abu Bakar; Erwhani, Indri; Hartono, Hartono (International Journal of Health Sciences, 2023)
The implementation of an K3 culture really depends on the employee's level of knowledge, workload and work environment. Workers know about the risks that may occur, but because there is no sanction from the company, workers do not comply with the use of Personal Protective Equipment (PPE) in implementing K3. The aim of this research is to determine the implementation of K3 in the form of employee personal protective equipment in terms of the knowledge, workload and work environment factors of employees at PT. Bahana Prima Nusantara. This research uses a qualitative method that digs deeper into the extent of the implementation of personal protective equipment in the K3 culture on employee productivity, where the number of informants is 5 people. As for the data collection method, it consists of primary data obtained from interviews, while secondary data is obtained from other supporting data. The conclusion from the research results is that workers' lack of knowledge has an impact on employee work productivity, excessive workload can affect employee productivity, and a comfortable and enjoyable work environment will form a productive work culture.